ANALISIS YURIDIS PENYALAHGUNAAN TRANSFER PRICING SEBAGAI SARANA PENGHINDARAN PAJAK DI INDONESIA - Oktavian; Sudarto; Rizky Pratama (Fakultas Hukum Universitas Kristen Indonesia, 2026)
This study examines the legal regulation of transfer pricing in Indonesia and its implications for tax avoidance practices by multinational enterprises. Transfer pricing is essentially a legitimate and necessary business mechanism for allocating costs and profits within a multinational group; however, in practice it is highly susceptible to abuse through profit shifting and base erosion. This research focuses on a normative legal analysis of Article 18 of the Indonesian Income Tax Law and Ministry of Finance Regulation No. 172/PMK.03/2023 as the latest umbrella regulation that consolidates Indonesia’s transfer pricing framework and aligns it with the OECD Transfer Pricing Guidelines. Using a statute and conceptual approach, the study analyzes the concepts of the Arm’s Length Principle, related-party relationships, and the enforcement mechanisms addressing abusive transfer pricing practices. The findings indicate that although PMK-172 has strengthened the normative framework and enhanced legal certainty, significant implementation challenges remain, particularly regarding divergent interpretations, the burden of proving the economic substance of related-party transactions, and the high volume of transfer pricing disputes before the Tax Court. Accordingly, the effectiveness of preventing tax avoidance through transfer pricing depends not only on comprehensive regulation but also on consistent enforcement and the quality of legal and economic analysis by tax authorities and the judiciary.